Perhitungan dan Visualisasi Alinyemen Horizontal - Sugiarto, Hansel Davin; Setiawan, Rudy; Budhi, Gregorius Satia (Prodi Teknik Sipil, Fakultas Teknik, Universitas Jember dan Forum Studi Transportasi antar Perguruan Tinggi, 2024)
Road geometry design is a design process that plans the physical form of road pavement, which will later be used as a benchmark during the construction process. One of the designs referred to is the horizontal alignment, which sometimes requires repeated calculations. This paper discusses applications created using Python programming language that can calculate azimuth and horizontal alignment and act as a preliminary design by providing a range of design specifications on radius and speed. Applications can also generate coordinates files that Unity can read for visualization. The level of accuracy in the azimuth calculation shows no significant difference from the manual calculation. In the horizontal alignment test, there is a difference in decimal numbers due to the tendency of rounding in manual calculations. Unity has displayed the bend and PI lines on the visual output by reading two